(untitled) - Kimbrough, Victoria (New York, 1998)
The book features core vocabulary, acarefully structured grammar syllabus, cross-cultural topics, key learning strategiesintegrated into each unit and consolidated in the Strategy Session review units
Keywords: English language; Spoken english,Problems, exercises, etc